Analysis of the Influence of AI on Student Learning Motivation in the Digital Era - Im, Rosdiana; Umasugi, Mohtar; Umasugi, Hamzah; Adam, Adiyana; Lumbessy, Sahabuddin; Juliadarma, Minggusta (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of the application of artificial intelligence (AI) on students' learning motivation in the digital era, focusing on the local context in North Maluku. Using a descriptive quantitative approach, data was collected through a survey involving 150 respondents from various educational institutions in Ternate. The results of the study show that the integration of AI in learning can increase student motivation through an interactive and adaptive approach, as well as enable personalization of the learning experience. AI-based applications, such as Grammarly and Turnitin, have been shown to improve student learning outcomes by between 15-25%. However, challenges such as over-reliance on technology and limited infrastructure in the region were also identified. This study recommends the development of technology-based education policies, continuous training for educators, and equitable access to technology infrastructure to maximize the benefits of AI in education. These findings are expected to contribute significantly to the development of educational policies that are relevant to contemporary needs.